Rapidly progressive cataract formation associated with non‐small‐cell lung cancer therapy. Issue 12 (December 2016) - Liu, Erica; Kopani, Kamden
Abstract : N/A: We report 6 patients who developed rapidly progressive hypermature cataracts after starting treatment with rociletinib, a non‐small‐cell lung cancer therapy with known side effects of hyperglycemia, fatigue, and prolonged QT. Early cataract detection and surgery may prevent complications during future cataract removal. Although rociletinib development has been suspended, there are patients who have been treated and will continue to be treated with this medication based on their physician's judgment. These physicians should know about the potential for rapid vision loss due to cataracts as a manageable side effect. Financial Disclosure : Neither author has a financial or proprietary interest in any material or method mentioned.